2016
DOI: 10.1039/c6ra19094d
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the role of transport velocity in biomotor-powered microtubule spool assembly

Abstract: We examined the sensitivity of microtubule spools to transport velocity. Perhaps surprisingly, we determined that the steady-state number and size of spools remained constant over a seven-fold range of velocities. Our data on the kinetics of spool assembly further suggest that the main mechanisms underlying spool growth vary during assembly.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 30 publications
1
7
0
Order By: Relevance
“…Because ATP concentration controls the kinesin step-rate at the molecular level, we expect the topological entropy and Lyapunov exponent to increase with increasing ATP concentration. When single microtubules glide on a kinesin-decorated glass surface, their gliding velocity as a function of ATP concentration is generally well described on a local level by Michaelis-Menten kinetics [42][43][44]. Similarly, we observed that the average v rms (Methods: PIV velocity analysis) for our attached beads also follows Michaelis-Menten kinetics under ATP variation, Fig.…”
Section: Bi-v)supporting
confidence: 67%
“…Because ATP concentration controls the kinesin step-rate at the molecular level, we expect the topological entropy and Lyapunov exponent to increase with increasing ATP concentration. When single microtubules glide on a kinesin-decorated glass surface, their gliding velocity as a function of ATP concentration is generally well described on a local level by Michaelis-Menten kinetics [42][43][44]. Similarly, we observed that the average v rms (Methods: PIV velocity analysis) for our attached beads also follows Michaelis-Menten kinetics under ATP variation, Fig.…”
Section: Bi-v)supporting
confidence: 67%
“…The tubulin solution was then incubated in a 37 °C bath for 12 hours to allow for polymerization after which microtubules are then stored at room temperature in a dark box. Recombinant penta-histidine-tagged kinesin protein was purified from e coli as previously described 19,20 . All other chemicals were purchased from Sigma Aldrich (St. Louis, MO, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Flow cells 19 for the experiments are constructed by placing two thin strips of tape on a glass slide. Glass was sonicated in Acetone, Methanol, Ethanol, and Nanopure water for 1 hour each and dried with N 2 gas.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations